Buckling of circumferentially corrugated cylindrical shells under uniform external pressure. (17th November 2019) - Zhang, Jian; Zhang, Shan; Cui, Weicheng; Zhao, Xilu; Tang, Wenxian; Wang, Fang
ABSTRACT: The paper focuses on the buckling of circumferentially corrugated cylindrical shells under uniform external pressure, along with the effects of corrugation on the buckling. The buckling of unstiffened and corrugated cylindrical shells are studied using a numerical method. The nonlinear numeric compares well with the existing experiment. Then, the buckling of triangle, half-circle, and sine corrugated shells are, respectively, presented, which demonstrates that the sine-shaped corrugation leads to best buckling pressure. Subsequently, several sine-shaped corrugated cylindrical shells with different corrugation amplitudes are evaluated. On this basis, preferred mass and volume equivalent corrugated shells are, respectively, used to make a comparison with the unstiffened cylindrical shell. Finally, the effects of diameter, thickness, and material properties on the buckling of preferred corrugated shells are, respectively, investigated. The results show that the circumferentially sine-shaped corrugation with the half period-to-amplitude ratio of 4.4 can enhance the buckling pressure of shell by more than four times.